Prevalence and Correlates of HIV Testing among Young People Enrolled in Non-Formal Education Centers in Urban Chiang Mai, Thailand: A Cross-Sectional Study - Musumari P. (2017)
© 2016 Musumari et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background HIV testing is the gateway to HIV prevention, treatment, and care. Despite the established vulnerability of young Thai people to HIV infection, studies examining the prevalence and correlates of HIV testing among the general population of Thai youth are still very limited. This study investigates socio-demographic, behavioral, and psychosocial factors associated with HIV testing among young Thai people enrolled in Non-formal Education Centers (NFEC) in urban Chiang Mai, Northern Thailand. Methods This was a cross-sectional quantitative study conducted among young unmarried Thai youth-between the ages of 15 and 24-who were enrolled in NFEC in urban Chiang Mai. Multiple logistic regressions were used to identify correlates of "ever tested for HIV" among the sexually active participants. Findings Of the 295 sexually active participants, 27.3% reported "ever tested for HIV;" 65.4% "did not consistently use condom;" and 61.7%"had at least 2 lifetime partners." We found that "selfefficacy" (AOR, 4.92; CI, 1.22'19.73); "perception that it is easy to find a location nearby to test for HIV" (AOR, 4.67; CI, 1.21'18.06); "having at least 2 lifetime sexual partners" (AOR, 2.05; CI, 1.09'3.85); and "ever been pregnant or made someone pregnant" (AOR, 4.06; CI, 2.69'9.15); were associated with increased odds of having ever been tested. On the other hand, "fear of HIV test results" (AOR, 0.21; CI, 0.08'0.57) was associated with lower odds of ever having been tested for HIV. Conclusion The main finding is that a substantially high proportion of Thai youth is engaged in risky sexual behaviors-yet reports low rates of ever having been tested for HIV. This highlights an urgent need to develop appropriate interventions-based on the identified correlates of HIV testing. There is also an urgent need to enhance HIV testing and to promote safer sexual behaviors among young Thai people-particularly those who are out-of-school.